Domestic/Family Homicide: A Systematic Review of Empirical Evidence. (July 2023) - Truong, Mandy; Yeganeh, Ladan; Cartwright, Anna; Ward, Emma; Ibrahim, Joseph; Cuschieri, Dominique; Dawson, Myrna; Bugeja, Lyndal
Background: Domestic/family homicide (D/FH) is a global social, economic and public health problem. To date, the research studies into risk factors associated with D/FH has largely focused on intimate partner homicide (IPH). A more contemporary approach recognizes that D/FH extends beyond the intimate partner relationship. This systematic review sought to identify and quantify the individual, relationship, community and societal factors in the empirical evidence literature on D/FH. Methods: Eight electronic databases were searched from January 1999 to December 2020. Published journal articles on studies of D/FH were included if the study included victims and/or perpetrator of D/FH, reported risk and/or protective factors associated with D/FH, reported primary data and was published in English. Factors were descriptively synthesized by the categories of the social ecological model and D/FH sub-type. Results: Three hundred and forty published articles met the inclusion criteria. From 1999 to 2020 the number of articles on D/FH increased globally from 10 to 40 respectively, declining to 23 in 2020. Almost half of the articles examined populations located in the Americas (160, 47.1%), predominately the United States and the majority of articles used quantitative designs (277, 81.5%). The forms of homicide more commonly studied were intimate partner (171, 50.3%), and filicide (98, 28.8%). Approximately 90% of articles reported individual victim and perpetrator factors, 64.7% examined relationship factors, 17.9% examined community factors and 15.6% examined societal factors. Conclusion: To inform universal and targeted D/FH elimination and prevention strategies, more research across different regions and a greater emphasis on community and societal-level factors is needed.